Perbandingan peranan Jalur Kredit Dan Jalur Tingkat Suku Bunga Pada Mekanisme Transmisi Kebijakan Moneter 1990-1999 = Comparative Role of Credit and Interest Rate Channels in Transmission Mechanism of Monetary Policy - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT The purpose of this study is to compare the role of credit and interest rate channels in transmission mechanism of monetary policy. This study will compare between short run (1990.1-1999.3) and long run (1997.1-1993.4) perspectives. Vector autoregressions (VAR) method is used for analyzing the data. The main uses of the VAR are causality, variance decomposition, and impulse response. The quarterly data used in this study are stationary in lagged first difference. The VAR model is estimated with two lags based on both the Akaike and Schwartz criteria. Credit channel model consists of three variables, real credit total (DL), consumer price index (DP), and real GDP (DY). Interest rate channel model consists of short run interest rate (DI), consumer price index (DP), and real GDP (DY). In the long run (1990.1-1999.3) and short run (1997.1-1999.3) estimates indicate that credit channel is better than interest rate channel in transmission mechanism. Finally, this study has a purpose to Bank of Indonesia to consider credit channel as dominant channel in transmission mechanism monetary policy in Indonesia. Keywords: Role of Credit -- Interest Rate -- Monetary Policy.